Vertical or horizontal force-velocity profile: which one is more sensitive to detect the fatigue induced by a basketball-specific protocol? - Li, Z.; Gao, L.; Zhang, X.; Deng, K.; Gu, Y.; Janicijevic, D.; García-Ramos, A. (Kinesiology, 2025)
This study aimed to determine which task (jumping or sprinting) and which force-velocity (F-V) relationship parameter (maximal force [F0], maximal velocity [v0], or maximal power [Pmax]) is the most sensitive indicator of fatigue induced by a basketball-specific protocol. Following a familiarization session, 19 junior male basketball players completed an experimental session in which both vertical (jumping) and horizontal (sprinting) F-V profiles were measured before, during and after undergoing a basketball-specific fatigue protocol (modified version of the Loughborough Intermittent Shuttle Test). All F-V relationship parameters, except horizontal F0 (p = .328), were significantly reduced after fatigue (p = .042). The vertical Pmax (ES = -0.48 to -0.80), horizontal Pmax (ES = -0.58 to -1.28), and horizontal v0 (ES = -0.81 to -0.98) showed larger reductions compared to the pre-fatigue assessment than the vertical v0 (ES = -0.19 to -0.27), vertical F0 (ES = -0.16 to -0.25), and horizontal F0 (ES = -0.11 to -0.30). When the percentage changes with respect to the pre-fatigue assessment were compared between the jumping and sprinting tasks, no significant differences in their magnitude (p = .364) and trivial to small correlations (-0.23 = r = 0.19) were detected. The results suggest that Pmax is the most suitable parameter to detect fatigue following a basketball-specific fatigue protocol, while the lack of significant correlations for the changes in F-V relationship parameters highlight the importance of measuring both the vertical and horizontal F-V profiles to gain comprehensive understanding of the changes in the mechanical properties of lower-body muscles following fatigue protocols.